The investigation of properties of elastomer materials filled with modified carbon black and coupling agent. - Yu. V. Kornev; A. M. Bukanov; O. B. Yumashev; V. A. Zhogin; Yu. A. Gamlitsky (Тонкие химические технологии, 2009)
Possibility of interaction between modified by proposed method carbon black and silane coupling agent is shown. It allows to optimize hysteresis properties of elastomer composites, while modified carbon black leads to increasing in its hardness at impact load.